2011
DOI: 10.1016/j.molcel.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

cIAPs Block Ripoptosome Formation, a RIP1/Caspase-8 Containing Intracellular Cell Death Complex Differentially Regulated by cFLIP Isoforms

Abstract: SummaryThe intracellular regulation of cell death pathways by cIAPs has been enigmatic. Here we show that loss of cIAPs promotes the spontaneous formation of an intracellular platform that activates either apoptosis or necroptosis. This 2 MDa intracellular complex that we designate “Ripoptosome” is necessary but not sufficient for cell death. It contains RIP1, FADD, caspase-8, caspase-10, and caspase inhibitor cFLIP isoforms. cFLIPL prevents Ripoptosome formation, whereas, intriguingly, cFLIPS promotes Ripopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
873
5
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 770 publications
(932 citation statements)
references
References 58 publications
32
873
5
3
Order By: Relevance
“…48, 49 Yet, we found that despite the efficiency of Tweak-induced c-IAP1/2 depletion in NIKdeficient MEFs, RIP1 and caspase-8 failed to assemble, indicating that TNFα-induced complex IIb formation is a highly regulated process that is primed by c-IAP1/2 depletion but requires the kinase NIK.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…48, 49 Yet, we found that despite the efficiency of Tweak-induced c-IAP1/2 depletion in NIKdeficient MEFs, RIP1 and caspase-8 failed to assemble, indicating that TNFα-induced complex IIb formation is a highly regulated process that is primed by c-IAP1/2 depletion but requires the kinase NIK.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, we showed that (1) Tweak/TNFα or agonist LTβR/TNFα stimulation led to caspase-8 and RIP1 interaction; (2) RIP1 kinase inhibition by Nec-1 inhibits cell death and blocks caspase-8 and RIP1 association; (3) cell death and RIP1/caspase-8 assembly are severely impaired in NIK-deficient MEFs stimulated with Tweak/TNFα A 2-MDa death-inducing complex containing the core components RIP1/FADD/caspase-8, referred as ripoptosome, was reported to form in response to genotoxic stress or to TLR3 activation in some cancer cell lines. 48,49 In both the studies, the authors found that the assembly of the ripoptosome occurred independently of TNFR1 signaling. However, in our experimental settings, a robust activation of NIK in the absence of TNFR1 stimulation could neither promote a NIK-associated caspase-8 activity nor an interaction between RIP1 and caspase-8.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested that apoptosis and necroptosis can be regulated by a newly defined RIP1, FADD and caspase-8 signalling platform termed the 'ripoptosome', which assembles in response to IAP inhibition by genotoxic stress or pharmacological agents ( Figure 5) (Feoktistova et al, 2011;Tenev et al, 2011). Unlike complex II, the ripoptosome does not originate from or require death receptor activation for assembly.…”
Section: Ripoptosome-a Novel Death-regulating Complexmentioning
confidence: 99%
“…However, the depletion of IAPs, that is, during genotoxic stress or Smac-mimetic treatments, derepresses RIP1 and allows its binding to FADD and caspase-8 to form the ripoptosome. The complex subsequently signals to downstream apoptotic and necroptotic pathways depending on the differential regulation of caspase-8 activity by cFLIP (Feoktistova et al, 2011;Tenev et al, 2011). In the absence of cFLIP, the ripoptosome signals to the apoptotic pathway.…”
Section: Ripoptosome-a Novel Death-regulating Complexmentioning
confidence: 99%
See 1 more Smart Citation